Monkey see, monkey do? Exploring parent-athlete behaviours from youth athletes' perspective - McCabe, Liam P.; Tsiros, Margarita D.; Crozier, Alyson J. (Frontiers in Sports and Active Living, 2024)
Parents are an important social agent that can shape their child's behaviour in sport. However, the association between a youth athlete's perception of their parent's sideline sport behaviour and their own sporting behaviours is currently unclear. Therefore, the purpose of the present study was to explore the relationship between parent and youth athlete behaviours in sport settings. Australian youth athletes (n = 67) participating in team-based sports completed an online survey where they reported their parents positive and negative sideline behaviours and their own prosocial and antisocial sport behaviour during the past month. Linear regression results suggested that parent's positive behaviours were associated with youth prosocial behaviours, whereas parent's negative behaviours were associated with youth antisocial behaviours. Results provide preliminary quantitative evidence that youth athletes' perceptions of their parents' sideline behaviours predict their own on-field behaviours. As antisocial athlete behaviours were positively associated with parent negative behaviours, sport organisations should target, and ideally eliminate, negative parent behaviours.Conversely, to improve prosocial athlete behaviour, encouraging positive parent behaviours should be promoted.• Positive sideline parent behaviours were frequently perceived, whereas negative sideline parent behaviours were rarely perceived by youth athletes • Positive sideline parent behaviours were linked with more prosocial youth behaviours towards both their teammates and opponents• Negative sideline parent behaviours were linked with more antisocial youth behaviours towards both their teammates and opponents